[The problem of Parkinsonism associated with the motor neuron disease. Clinical report on 11 sporadic cases (author's transl)] - Perticoni, G; Pezzella, F; Ferroni, A (1980)
The clinical data are presented of 11 subjects affected by a sporadic form of Parkinsonism with associated motor neuron disease. Combined lesions of upper and lower neuron were found in 10 of 11 cases, while in the remaining case only lower motor neuron disorder was present. The female/man ratio is 1/11. The early symptoms appear at a mean age of 56.9 years: in 6 patients with both syndromes at the same time while in 4 only with Parkinson. These observations confirm the view that different degenerative neurological syndromes must not be considered autonomous entities, but only different forms of polysystemic degenerative diseases that choose, in particular conditions, some neuronal districts rather than others.